INVESTIGATING THE SPEECH FUNCTION OF NOVICE VERSUS EXPERIENCED TEACHERS’ TALKS IN EFL CLASSROOM AT SMA PANCASILA BENGKULU - Akbarjono, Ali; Martina, Feny; Kurniati, Anggun (Yayasan Darussalam Bengkulu, 2020)
This study deals with the teachers’ talk of the EFL classroom of SMA Pancasila Bengkulu. It aims to describe the types of speech functions used by English teachers in the EFL classroom of SMA Pancasila Bengkulu, to find out the most dominant type used by English teachers in EFL classes at SMA Pancasila Bengkulu, and to describe the reasons why English teachers use speech function differently in EFL classroom. This thesis research was conducted using a descriptive qualitative. Researchers used triangulation data collection techniques, namely observation, audiovisual material, and interviews. Data transcription is classified into six basic types of speech function. There are expressive, directive, referential, metalinguistic, poetic, and phatic. The researcher observed two English teachers at SMA Pancasila Bengkulu. From the two teachers observed, the researcher found different total utterances and percentages. The total utterances of the two teachers were 80 utterances classified into six types of speech functions. The most dominant type used by all teachers is the referential function. There are 28 utterances out of 80 utterances (35%) which are classified as referential functions. Why they use the speech function differently is because each type of speech function has a different function that must be adapted to different conditions and situations in the classroom.